NATURAL ADMIXTURE AS AN ALTERNATIVE FOR CHEMICAL ADMIXTURE IN CONCRETE TECHNOLOGY: A REVIEW - FAQE, HERSH; DABAGHH, HOSHANG; MOHAMMED, AZAD (Journal of Duhok University, 2021)
The use of chemical admixtures in concrete is a common practice in modern construction. Although chemical admixtures improve the properties of concrete but also create leaching problem and they are responsible for environmental pollution. The Impact of chemical admixture on environmental can occur when chemical admixtures are exposed to the environment or when dumping concrete granulate containing admixtures after the demolition of a structure or when concrete granulate is used as gravel replacement in construction and as the concrete admixtures are very readily soluble in water, hence create an environmental problem due to leaching. This paper presents a critical review of several natural materials used in concrete as an admixture that influences the mechanical and durability properties of concrete. This kind of admixtures can be considered as an eco-friendly one with regard the impact on the environment and of low cost compared with the chemical admixture